2010
DOI: 10.1089/jwh.2009.1393
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cervical Cancer Screening Among Lesbians

Abstract: Objective: To evaluate cervical cancer screening practices and barriers to screening in a sample of lesbians. Methods: Cross-sectional survey data were collected from 225 self-identified lesbians who completed an online questionnaire. Results: Of the respondents, 71% reported receiving a Pap screening test in the past 24 months (routine screeners), and 29% reported receiving a Pap screening test >24 months ago or never (nonroutine screeners). Routine screeners were more likely to be older ( p < 0.01), white ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 40 publications
6
94
1
3
Order By: Relevance
“…Regarding the demand for health services, among the six lesbians interviewed, there was no demand for preventive cervix and breast cancer screenings, for example. In Brazil and other countries, research revealed signifi cant proportions of lesbians who did not undergo routine cervical cancer screenings 3,26 . A survey conducted on homosexual and bisexual women in Brazil stated that the diffi culties reported by the subjects concerning preventive examinations were discomfort and embarrassment related to gynaecological examinations, the lack of health services capable of dealing with particular demands of lesbian women, and the unpreparedness of health professionals towards the health needs of lesbians 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the demand for health services, among the six lesbians interviewed, there was no demand for preventive cervix and breast cancer screenings, for example. In Brazil and other countries, research revealed signifi cant proportions of lesbians who did not undergo routine cervical cancer screenings 3,26 . A survey conducted on homosexual and bisexual women in Brazil stated that the diffi culties reported by the subjects concerning preventive examinations were discomfort and embarrassment related to gynaecological examinations, the lack of health services capable of dealing with particular demands of lesbian women, and the unpreparedness of health professionals towards the health needs of lesbians 27 .…”
Section: Discussionmentioning
confidence: 99%
“…(4,6) In Australia, the 3-year rate is a little lower at 70%. (7) Non-attendance for screening is the second most attributable risk factor for invasive cervical cancer (8,9) as it puts women at a higher risk of late diagnosis of cervical cancer which leads to a poorer prognosis. (9) In the 12 years following the introduction of the Australian national screening program in 1991 there was a 33% reduction in the incidence of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Lack of access to appropriate care may be a particularly salient barrier in the southern USA, where attitudes towards LGBT-identified individuals are perceived to be especially unwelcoming due to the region's religious and political conservatism. 12 African-American women who have sex with women are emerging as a relatively hidden LGBT subpopulation that is at especially high risk for negative sexual health outcomes 13 as a result of their multiple structural inequalities (i.e.…”
Section: Introductionmentioning
confidence: 99%